2011
DOI: 10.1016/j.ophtha.2010.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Documentation of Intraretinal Retinal Pigment Epithelium Migration via High-Speed Ultrahigh-Resolution Optical Coherence Tomography

Abstract: PURPOSE-To describe the features of intraretinal retinal pigment epithelium (RPE) migration documented on a prototype spectral domain high speed, ultrahigh resolution optical coherence tomography (OCT) device in a group of patients with early to intermediate dry age-related macular degeneration (AMD). To correlate intraretinal RPE migration on OCT to RPE pigment clumping on fundus photographs. DESIGN-Retrospective, non-comparative, non-interventional case series. PARTICIPANTS-Fifty METHODS-3DOCT scan sets fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
113
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(114 citation statements)
references
References 20 publications
1
113
0
Order By: Relevance
“…Several in vivo OCT studies have suggested that HRF in intermediate AMD eyes may represent the migration of activated RPE cells into the inner retinal layers. 5,8,20,21 This hypothesis was supported by some laboratory studies that demonstrated the potential ability of RPE cells to migrate when induced by cytokines and other inflammatory mediators in response to oxidative damage and complement activation. 22,23 Previous studies 7,24 showed that HRF in AMD were associated or colocalized with the drusen apex and showed an increased association with RPE atrophy at baseline, 24 or if atrophy was not already present, with an increased risk of developing atrophy at that location.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Several in vivo OCT studies have suggested that HRF in intermediate AMD eyes may represent the migration of activated RPE cells into the inner retinal layers. 5,8,20,21 This hypothesis was supported by some laboratory studies that demonstrated the potential ability of RPE cells to migrate when induced by cytokines and other inflammatory mediators in response to oxidative damage and complement activation. 22,23 Previous studies 7,24 showed that HRF in AMD were associated or colocalized with the drusen apex and showed an increased association with RPE atrophy at baseline, 24 or if atrophy was not already present, with an increased risk of developing atrophy at that location.…”
Section: Discussionmentioning
confidence: 76%
“…5 It has been demonstrated that there is a highly specific spatial correlation of HRF with the apex of drusen 6 and/or subretinal drusenoid deposits (SDD) 4 and that HRF overlying drusen are associated with an increased risk of atrophy at that location. 7 The AREDS2 Ancillary SD-OCT Study reported that GA lesions detected at 2 years were significantly correlated with the presence of HRF and with a greater number of HRF at baseline.…”
mentioning
confidence: 99%
“…79,80,82 Focal areas of RPE loss or depigmentation may be demonstrated by choroidal hypertransmission, 5 and pigment clumping and migration may be identified as outer retinal hyperreflective foci.…”
Section: Retinal Pigment Epithelium Abnormalitiesmentioning
confidence: 99%
“…There is now a clear trend of extended interests towards the application side in addition to the technology development. Currently, the well established ophthalmic diagnostic application occupies about 50% of academic and industrial shares in OCT business [10][11][12][13][14][15][16][17][18][19] . Cardiovascular imaging [20][21][22][23][24][25][26][27] has become the next big thing when the coronary OCT products have seen FDA clearance in the United States.…”
Section: Introductionmentioning
confidence: 99%